Pengembangan Model Pendidikan Berbasis Integrasi Ilmu Dan Islam Di Universitas Islam Riau - Yenni Yunita; Karim, Nazir; Alpizar, Alpizar (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2025)
Abstract Riau Islamic University was established in 1962 with the main objective of integrating Islamic values ​​in the implementation of higher education. Since its inception, UIR has been committed to eliminating the dichotomy between general knowledge and religious knowledge, as well as overcoming the secularization of knowledge. This study aims to develop an educational model based on the integration of knowledge and Islam at Riau Islamic University. This type of research is research and development (Research and Development) or R & D which uses the ADDIE model. The results of this study are First, the concept of integrating Islam and knowledge has existed since the establishment of this campus. Several educational values ​​that can be integrated into knowledge are spread across various courses, including: (1) Morals, described as 6 values: Sincerity, Honesty, Trustworthiness, Kindness, Togetherness, and Justice. (2) Knowledge, described as 2 values: Intelligence and Hard work. (3) Charity, described as the value of preaching. Second, the Education Model based on "ISI (Integration of Science and Islam)" offers how to integrate science with Islam or vice versa. This can be done first by using Nash/text in the form of Verses or Hadith, namely conveying learning of study materials/science materials by explaining verses of the Qur'an or Hadith that are relevant to the science theory being taught. Second, using an analysis model that is Imani or Syar`i, namely conveying learning of science materials by explaining aspects of faith or sharia contained or relevant to science materials. Keywords: Model, Education, Integration of Science and Islam. Abstrak Universitas Islam Riau didirikan pada tahun 1962 dengan tujuan utama mengintegrasikan nilai-nilai Islam dalam penyelenggaraan pendidikan tinggi. Sejak awal berdirinya, UIR berkomitmen untuk menghilangkan dikotomi antara ilmu pengetahuan umum dan ilmu agama, serta menanggulangi sekularisasi ilmu pengetahuan. Penelitian ini bertujuan untuk mengembangkan model pendidikan berbasis integrasi ilmu dan Islam di Universitas Islam Riau. Jenis penelitian ini yaitu penelitian dan pengembangan (Research and Devlopment) atau R & D yang menggunakan model ADDIE. Hasil penelitian ini adalah Pertama, konsep integrasi Islam dan ilmu sudah ada sejak berdirinya kampus ini. Beberapa nilai Pendidikan yang bisa di integrasi dalam ilmu pengetahuan tersebar dalam berbagai mata kuliah diantranya: (1)Berakhlak, dijabarkan menjadi 6 nilai: Keikhlasan, Kejujuran, Amanah, Kebaikan, Kebersamaan, dan Keadilan. (2) Berilmu, dijabarkan menjadi 2 nilai: Kecerdasan dan Kerja keras. (3) Beramal, dijabarkan menjadi nilai dakwah. Kedua, Model Pendidikan berbasis “ISI (Integration of Science and Islam)” ini menawarkan bagaimana cara mengintegrasikan ilmu pengetahuan dengan Islam atau sebaliknya. Hal ini bisa di lakukan pertama dengan menggunakan Nash/teks berupa Ayat atau Hadis, yaitu menyampaikan pembelajaran bahan kajian/materi sains dengan menjelaskan ayat Al-Quran atau Hadis yang relevan dengan teori sains yang diajarkan. Kedua, menggunakan model analisis yang bersifat Imani atau Syar`i, yaitu menyampaikan pembelajaran materi sains dengan menjelaskan aspek akidah atau syari`ah yang terkandung atau relevan dengan materi sains. Kata Kunci: Model, Pendidikan, Integrasi Ilmu dan Islam,